Antipiretik Ekstrak Etanol Daun Kemangi Aceh (Ocimi sancti folium) Pada Mencit - Ria Ceriana; Nora Elsaputri; Riska Nadia; Syifa Yulia; Indah Indah; Siti Mulyana; Elvita Meivianthy; Nisaul Fitria; Nisa Ulfitria; Siti Raihan Utami (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Traditional medicine or herbal medicine is widely used by ordinary people because it is considered safer than the use of modern medicine. This is because traditional medicine has fewer side effects than modern medicine. The purpose of this study was to observe the antipyretic effect of the ethanolic extract of basil leaves on mice. The experimental design in this study used a completely randomized design (CRD) where there were 4 treatments and 4 replications. The treatments in this study were control/P0 (not vaccinated and given extract), P1 (mouse vaccinated and given 0.5 ml of basil leaf extract), P2 (mouse vaccinated and given 0.7 ml of basil leaf extract), P3 (mouse vaccinated and given aquadest). The results showed that the body temperature of the mice that had increased due to the DPT vaccine had decreased after being given basil leaf extract. The P2 treatment, namely the extract treatment as much as 0.7 ml gave a significant effect on reducing the body temperature of mice